2019
DOI: 10.1186/s11671-019-2882-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Magnetofection of Magnetic Polyethylenimine Nanoparticles into MG-63 Osteoblasts Using a Novel Uniform Magnetic Field

Abstract: This study aimed to improve the magnetofection of MG-63 osteoblasts by integrating the use of a novel uniform magnetic field with low molecular weight polyethylenimine modified superparamagnetic iron oxide nanoparticles (PEI-SPIO-NPs). The excellent characteristics of PEI-SPIO-NPs such as size, zeta potential, the pDNA binding and protective ability were determined to be suitable for gene delivery. The novel uniform magnetic field enabled polyethylenimine-modified superparamagnetic iron oxide nanoparticles/pDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Cen and colleagues also showed that the transfection efficiency of PEI-ION/pDNA complexes into human osteosarcoma cells (MG-63) was significantly increased by the application of a uniform magnetic field (about four-fold increase) [ 392 ]. Moreover, they found that by changing from a non-uniform to a uniform magnetic field, the efficiency doubled to 42.1% [ 392 ]. In the same way, Vaca and colleagues studied the effect of MF time and the culture-to-magnet relative position on the transfection efficiency and cellular uptake [ 381 ].…”
Section: An Overview Of Ion-mediated Transfection In Gene Editingmentioning
confidence: 99%
“…Cen and colleagues also showed that the transfection efficiency of PEI-ION/pDNA complexes into human osteosarcoma cells (MG-63) was significantly increased by the application of a uniform magnetic field (about four-fold increase) [ 392 ]. Moreover, they found that by changing from a non-uniform to a uniform magnetic field, the efficiency doubled to 42.1% [ 392 ]. In the same way, Vaca and colleagues studied the effect of MF time and the culture-to-magnet relative position on the transfection efficiency and cellular uptake [ 381 ].…”
Section: An Overview Of Ion-mediated Transfection In Gene Editingmentioning
confidence: 99%
“…However, magnetic transfection was used in this study, which forced the transfection vector and the target cell to stay in contact. In addition, the oscillation induced by magnetic transfection on the target cell surface can cause the nanoparticle complex to move, which helps increase the transfection rate by mechanically stimulating endocytosis [ 30 , 46 , 47 ]. Other researchers have shown that magnetic transfection can effectively increase the transfection rate of gene vectors [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In aqueous environment, spermine residues in DSASP-NPs are localized outside the micelle formation due to its hydrophobicity property. Considering to cell membrane negatively charged, the positively charged complexes facilitate its cellular uptake [41].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of stability in formation of polycations-based nanocomplexes with negative phosphate backbone charge of DNA is considered as a substantial requirement in gene delivery applications to achieve proper transfection efficiency. Preparation of various weight ratio of polycations to DNA is assumed as one of the most significant parameters to achieve this process [41,45]. So, a different mass ratio of DSASP was mixed with similar volumes of pDNA and then results were analyzed based on gel retardation assay.…”
Section: Discussionmentioning
confidence: 99%